Reviews (XXI Century. Spanish Literature and Culture, 2005)
Ken Benson, Fenomenología del enigma. Juan Benet y el pensamiento literario postestructuralista. Ámsterdam, New York: Rodopi, 2004. 406 pp.Marga Piñero. La creación teatral de José Luis Alonso de Santos. Madrid: Fundamentos, Monografías RESAD, 2005, 446 pp.Sobejano-Morán, Antonio. Metaficción española en la postmodernidad. Kassel: Edition Reichenberger, 2003.Folkart, Jessica A. Angles on Otherness in Post-Franco Spain: The Fiction of Cristina Fernández Cubas. Lewisburg: Bucknell University Press, 2002.Eloy E. Merino y H. Rosi Song (eds.) Traces of Contamination: Unearthing the Francoist Legacy in Contemporary Spanish Discourse. Lewisburg,Pennsylvania: Bucknell University Press, 2005.
Keywords: Review